The addict as victim: Producing the 'problem' of addiction in Australian victims of crime compensation laws - Seear, K.; Fraser, Suzanne (Elsevier BV, 2014)
Background: Much academic scholarship has explored drug use and ‘addiction’ in the criminal justice system. Methods: This paper explores what happens when ‘addicts’ are victims, through an analysis of victims of crime compensation case law within the state of Victoria, Australia. Results: We argue that the law enacts a set of unexamined assumptions about the ‘problem’ of addiction, including the assumption that it is incompatible to be both addict and victim. However, courts reconcile this ‘dilemma’ by explaining addiction as an ‘effect’ of trauma, violence or abuse, a seemingly sympathetic rendering of addiction. Although this appears to represent a less stigmatising approach than found in the criminal law, we argue that these processes actually produce new challenges for people who use drugs and ‘addicts’, and that these may be counter to the stated aims and objectives of crimes compensation law. We argue that even legal systems with an explicitly remedial rationale have the potential to generate harms, creating those who use drugs and ‘addicts’ as pathological in certain ways and thereby undermining their claims to citizenship. Our analysis is underpinned by a critical approach to the constitution of social problems based on the work of Carol Bacchi. Conclusion: Although the focus is on Australian law, the arguments we develop in this paper are likely to resonate beyond the specific jurisdiction reviewed here, and raise questions about the mutually interdependent role of law and policy in compounding the stigmatisation and marginalisation of people who use drugs and drug ‘addicts’.